2000
DOI: 10.1111/j.1749-6632.2000.tb06603.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of DNA in the Plasma of Septic Patients

Abstract: Small amounts of plasma-free DNA have been observed both in healthy individuals and in patients with various diseases such as systemic lupus erythematosus, rheumatoid arthritis, viral hepatitis, and cancer. This communication demonstrates that septic patients also release DNA in plasma. After DNA extraction from plasma, exon 1 of the K-ras gene was amplified by PCR and products were analyzed by dot-blot hybridization. Plasmas from polytraumatic patients and control healthy individuals were used for comparisons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…Healthy individuals typically display very low levels of cf-DNA in circulation. In sepsis enhanced apoptosis [19] and cell necrosis [20] result in elevated cf-DNA levels [21]. A recent study by Dwivedi et al showed a very high discriminative capability of cf-DNA to predict mortality among ICU patients with severe sepsis [14].…”
Section: Discussionmentioning
confidence: 99%
“…Healthy individuals typically display very low levels of cf-DNA in circulation. In sepsis enhanced apoptosis [19] and cell necrosis [20] result in elevated cf-DNA levels [21]. A recent study by Dwivedi et al showed a very high discriminative capability of cf-DNA to predict mortality among ICU patients with severe sepsis [14].…”
Section: Discussionmentioning
confidence: 99%
“…23,31,33 This may increase the ability to measure certain biomarkers of NETs in plasma. Indeed, DNA 75 and nucleosomes 76 are elevated in septic patients, and cell-free DNA levels were a better predictor of progression to sepsis after traumatic injury than interleukin-6 or C-reactive protein, markers of inflammation. 77 MPO-DNA complexes are elevated specifically during active disease in patients with small-vessel 25 when their thrombotic risk is the highest.…”
Section: Nets In Human Thrombosismentioning
confidence: 99%
“…Since its discovery, cfDNA has been found to be increased in a variety of neoplastic and non-neoplastic diseases of humans, including myocardial infarction (Chang et al 2002), rheumatoid arthritis (Zhong et al 2007), severe viral infections (Ha et al 2011), stroke , sepsis (Martins et al 2000;Rhodes et al 2006) and severe trauma (Lo et al 2000;Lam et al 2003;Macher et al 2012). In all these diseases, the cfDNA concentrations have correlated with disease severity and prognosis.…”
Section: Introductionmentioning
confidence: 99%